2018
DOI: 10.1007/s11259-018-9719-z
|View full text |Cite
|
Sign up to set email alerts
|

A long term feed supplementation based on phosphate binders in Feline Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a very common disorder in elderly cats. A proper renal diet represents the most efficient therapeutic intervention to improve survival and life quality in feline patients with 3 and 4 International Renal Interest Society (IRIS) stages. Twenty cats were selected in this study. Ten were administered the dietary supplementation for 360 days and the other ten, whose owners did not give consent for any supplemental therapies apart from the renal diet, were selected from a clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…In addition, the values were recorded at 4-8 weeks following the supplement administration (Zatelli et al, 2012). A more recent study, showed that another type of dietary supplement reduced significantly serum phosphorus and increased HCO 3 values in cats with CKD, improving their clinical conditions, without any adverse reaction (Biasibetti et al, 2018). In our study, the dogs treated with dietary supplementation showed a significant reduction in serum phosphorus level and an increase in HCO 3 compared to the control group (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…In addition, the values were recorded at 4-8 weeks following the supplement administration (Zatelli et al, 2012). A more recent study, showed that another type of dietary supplement reduced significantly serum phosphorus and increased HCO 3 values in cats with CKD, improving their clinical conditions, without any adverse reaction (Biasibetti et al, 2018). In our study, the dogs treated with dietary supplementation showed a significant reduction in serum phosphorus level and an increase in HCO 3 compared to the control group (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…1). In literature, hypercalcemia has been reported in animals receiving calcium-based phosphate binders, and it is considered as an adverse event (Biasibetti et al, 2018). The phosphate binders used in our supplement were chitosan, calcium lactate gluconate and calcium carbonate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations